Seconded National Experts and global mobility - extending the paradigm - Renshaw, Phil St John; Parry, Emma; Dickmann, Michael (Cranfield University, 2017)
Global mobility is an expanding field of academic research, which identifies an increasing range of modern variants of people working abroad. The community of Seconded National Experts (SNEs) in the institutions, bodies, and agencies of the European Union (EU) is a distinct category of internationally mobile employees, which has so far been neglected. This article assesses the features of this influential group of people and compares them to other communities within the generally recognized expatriate community. The unique nature of SNEs and hence the challenges that need to be considered by human resource (HR) practitioners to ensure they achieve their desired goals at organizational and individual levels are identified. The findings suggest that expatriate typologies should be extended to include this unique community and provide further guidance to HR practitioners. Finally, areas for additional research are offered, with the aim of learning from SNEs to extend international assignment theory.
Keywords: global mobility; international assignments; Seconded National Experts